2023
DOI: 10.26434/chemrxiv-2023-zbqlc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural Determinants of the Catalytic Nia-L Intermediate of [NiFe]-Hydrogenase

Abstract: [NiFe]-hydrogenases catalyze the reversible cleavage of H2 into two protons and two electrons at the inorganic heterobimetallic NiFe center of the enzyme. Their catalytic cycle involves at least four intermediates, some of which are still under debate. While the core reaction, including H2/H- binding, takes place at the inorganic cofactor, a major challenge lies in identifying those amino acid residues that contribute to the reactivity and how they stabilize (short-lived) intermediate states. Using cryogenic i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 57 publications
(104 reference statements)
3
6
1
Order By: Relevance
“…(31)). The proton transfer to Cys68L (3G1, -4.1 kcal mol -1 , Figure S8) is also exergonic, suggesting that the proton could populate different rotameric configurations of both Cys374L and Cys68L, consistent with the experimentally observed multiple forms of the Ni-L state (46,47). However, in contrast to the energetically favored Glu21L-mediated pathway, we find that the His75L-mediated proton transfer to the cluster is strongly endergonic (Figure S8 (48).…”
Section: -S7 and Table S5-s7)supporting
confidence: 80%
See 1 more Smart Citation
“…(31)). The proton transfer to Cys68L (3G1, -4.1 kcal mol -1 , Figure S8) is also exergonic, suggesting that the proton could populate different rotameric configurations of both Cys374L and Cys68L, consistent with the experimentally observed multiple forms of the Ni-L state (46,47). However, in contrast to the energetically favored Glu21L-mediated pathway, we find that the His75L-mediated proton transfer to the cluster is strongly endergonic (Figure S8 (48).…”
Section: -S7 and Table S5-s7)supporting
confidence: 80%
“…We note that several structural models for the Ni-L (46,47) and Ni-R (23,56,57) states have been reported based on spectroscopic signatures, and indicating different structural isomers. For instance, temperature-dependent FTIR studies of the soluble [NiFe] hydrogenases observed protonation/deprotonation of the residue homologous to Cys374L (Cys546 in DvMF) with an ΔH and ΔS of 1.5 ± 0.8 kcal mol -1 and 6.1 ± 10.3 kcal mol -1 K -1 , suggesting that the cysteine residue can indeed undergo protonation change in the Ni-L state (46).…”
Section: Discussionmentioning
confidence: 74%
“…Investigations of the Ni−C to Ni a −SI interconversion by transient spectroscopy lend strong support for a concerted process, 31,32 and recent studies of the regulatory hydrogenase from Cupriavidus necator by cryo-IR and EPR produced a particularly detailed picture of the proton-transfer steps in that enzyme, elaborating on the pathway shown in Figure 2A. 38 The crucial cysteine both coordinates Ni and serves as a H + mediator. An attractive approach for probing the role of a cysteine-S atom is to exchange the cysteine for a selenocysteine (Sec, one-letter code U) by recombinant methods.…”
mentioning
confidence: 90%
“…The Ni−C state is in tautomeric equilibrium with Ni(I) species known collectively as Ni−L: IR spectroscopic studies have revealed that both Ni−L and Ni−R exist in several forms, differing in the location of the H + that has migrated locally without leaving the enzyme. 32,33,35,38 The Ni−L species form upon illumination at low temperature, but their detection under normal catalytic conditions has largely been restricted to O 2 -tolerant [NiFe] hydrogenases, suggesting that the equilibrium otherwise strongly favors Ni−C. 33,38,42,43 During H 2 oxidation, Ni−C is converted to a Ni(II) form known as Ni a − SI.…”
mentioning
confidence: 99%
See 1 more Smart Citation